Manajemen Nyeri Pada Pasien Dengan Fraktur Tibia Fibula: Studi Kasus - Sinuraya, Elida; Situmorang, Jastro; Sitinjak, Rivero N (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
Accidents often result in fractures. A tibia-fibula fracture will show bone discontinuity and damage to the surrounding tissue, causing complaints of pain. Pain management will prevent, reduce or stop the sensation of pain and increase a sense of comfort. This study used a qualitative research method with a case study approach.The purpose of this study was to describe pain management in patient with tibia-fibula fractures. The participant in this study was a 24 year old male with a fracture of the tibia and fibula. Participants complained of pain in the right leg and heel after an accident. Data were collected by three methods consist of observations, interviews, and documentation. Intervention in this study was pharmacological and non-pharmacological therapy such as building a trusting relationship, teaching distraction and relaxation techniques and placing participants in a comfortable position. Results - there was a decrease in pain levels from 7 to 3, participants stated that there was a decrease in pain, he were able to control the pain, and he could rest well